Effect of nickel (II) and cobalt (II) mixture on aerobic sludge biomass. Issue 2 (2021) - Negi, Rajhans; Kumar, Rajneesh; Jawed, Mohammad
Abstract : Improper waste management is leading to heavy-metal contamination in domestic waste water, particularly in developing countries. This study examined the impacts of a 1:1 (w/w) mixture of nickel (Ni) and cobalt (Co) metal ions on reactor performance, metabolic activity and sludge biomass characteristics in sequential batch reactors (SBRs). The study also investigated the recovery potential of sludge biomass, when the metal ions were discontinued from the feed. Two sets of four identical SBRs labelled as RMix0 (control), RMix5, RMix25 and RMix75 were fed with a carbon (C) source and a mixture of nickel (II) + cobalt (II) metal ions in concentrations of 0, 5, 25 and 75 mg/l, respectively. The SBRs were operated with a cycle time of 12 h. The two phases consecutively investigated were the stressed phase (metals present in the feed) for 21 days and the recovery phase (metals absent in the feed) for 14 days. The results showed that during the stressed phase, chemical oxygen demand removal and metabolic activity in RMix25 and RMix75 deteriorated. Settling characteristics and biomass morphology underwent severe changes in RMix25 and RMix75. On the basis of the results, the study suggests monitoring the settling characteristics of biomass for early indication of metallic infiltration as a damage prevention strategy for sludge biomass in a waste-water-treatment plant.